2020
DOI: 10.18502/ijph.v49i5.3226
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Remedies for Acne Vulgaris from the Viewpoint of Persian Medicine

Abstract: The article's abstract is no available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Sugary sweets, refined grains, a lot of protein, fatty dairy products, and a lot of sugar are all hallmarks of the Western diet. Obesity, insulin resistance, and acne are so prevalent in younger generations at alarming rates [16]. Anabolic androgen precursors of dihydrotestosterone (DHT), such as 5-pregnanedoine and other exogenous steroid hormones, are known to be present in cow's milk [15].…”
Section: Review Of Literature: Acne Vulgarismentioning
confidence: 99%
See 1 more Smart Citation
“…Sugary sweets, refined grains, a lot of protein, fatty dairy products, and a lot of sugar are all hallmarks of the Western diet. Obesity, insulin resistance, and acne are so prevalent in younger generations at alarming rates [16]. Anabolic androgen precursors of dihydrotestosterone (DHT), such as 5-pregnanedoine and other exogenous steroid hormones, are known to be present in cow's milk [15].…”
Section: Review Of Literature: Acne Vulgarismentioning
confidence: 99%
“…The Outward Signs of Acne vulgaris in Clinical Practice Nodules, pustules, comedones, and inflammatory papules are the typical lesions seen in acne. Cysts were the old name for some of the bigger nodules, and nodulocystic was a word for more severe inflammatory acne [16]. Comedones, both open and closed, are acne lesions that do not cause inflammation.…”
Section: Review Of Literature: Acne Vulgarismentioning
confidence: 99%
“…According to Persian medicines textbooks, Prunus domestica L., Tamarindus indica L., Terminalia chebula L., Ziziphus jujube L., and Cassia fistula L. may be effective in acne treatment (10). In addition, in recent studies, these medicinal plants have been demonstrated to be effective in treating acne lesions due to their antibacterial and anti-inflammatory effects (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%